SOUTH AND NORTH KHOREZM EPIC SCHOOLS (International journal of artificial intelligence, 2025)
In this article we will talk about Khorezm epic schools and their peculiarities. It is said that the ethnogenetic history of the people has a significant impact on the formation of different schools of epic poetry, as any ethnic group preserves its ancient traditions, which can be clearly seen in the epic schools of Khorezm.Also, art critic B.Matyokubov in his pamphlet divided the Khorezm epic into three shops based on the information given by Bola Bakhshi, folklorist S.R.Ruzimbaev also commented on Khorezm epics, Bakhshi schools, and there are two traditions of epic poetry in the oasis. The article is analyzed on the basis of the classification of traditions of epic poetry of South and North Khorezm, the similarities and differences of epic schools are proved by examples taken from Khorezm epics.